Discourse is cultural: New approaches to discourse analysis in the 'Non-West'. (September 2016) - Clark, Adam Scott
Abstract: A review article on two recent books arguing that Western techniques of discourse analysis are unsuited to the discourses of Asia, Africa and Latin America. The review article asks whether Shi-Xu, sole author of the earlier book and one of a trio of authors of the later one, has tacitly changed his view or has contradicted himself concerning whether his proposed Chinese Discourse Analysis is culture specific or applicable to anywhere in the 'non-West'. The review article strives to balance recognition of the books' positive contributions with honest acknowledgement of logical weaknesses. Highlights: Reviews two recent books discussing discourse analysis in the 'non-West.' Asks if the books change the way we approach discourse in specific settings. Balances the books' positive contributions with acknowledgement of weaknesses.